Propuesta de estrategia de macrorreglas para mejorar el desempeño de comprensión textos en estudiantes de segundo grado de secundaria - Guzman Zavaleta, Lily Deysi (2021)
This work has been prepared for students of the second grade, secondary education in the _x000D_ year 2019, with the topic entitled: Proposal of a macro-rules strategy to improve the _x000D_ performance of text comprehension in second-grade secondary school students. This _x000D_ learning session it is intended to achieve in students the ability to identify the theme, ideas _x000D_ and purpose of the text, selecting the criteria and the appropriate macro-rule._x000D_ Regarding the theoretical support, the main contributions of the authors and MINEDU _x000D_ documentation have been taken into consideration both for the management of teaching _x000D_ practice and for the development of the Communication area. This frame of reference has _x000D_ made it possible to support the information collected and provide support to teachers in _x000D_ their work._x000D_ For the pedagogical support, it was characterized by a reflection on the methodology used _x000D_ in the understanding of texts in the learning and teaching process, under a situational _x000D_ approach. Likewise, the cognitive approach is also assumed as the basis of pedagogical _x000D_ practice, competence assessment and formative assessment._x000D_ Consequently, the work is affirmed in the development of the learning session under the _x000D_ competence approach, thus achieving assuming the importance of teacher planning, the _x000D_ identification of significant situations according to the context and transversal approaches, _x000D_ as well as the management of the different learning strategies. All this, based on the _x000D_ competencies, capacities, and performance of the Communication area.